The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1128/iai.00210-19
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a 19-Amino-Acid Region in Clostridioides difficile TcdB2 Results in Spontaneous Autoprocessing and Reduced Cell Binding and Provides a Nontoxic Immunogen for Vaccination

Abstract: Clostridioides difficile toxin B (TcdB) is an intracellular toxin responsible for many of the pathologies of C. difficile infection. The two variant forms of TcdB (TcdB1 and TcdB2) share 92% sequence identity but have reported differences in rates of cell entry, autoprocessing, and overall toxicity. This 2,366-amino-acid, multidomain bacterial toxin glucosylates and inactivates small GTPases in the cytosol of target cells, ultimately leading to cell death. Successful cell entry and intoxication by TcdB are kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It has been reported that the CROPs-truncated TcdA and TcdB underwent moderately increased InsP6-induced autocleavage compared to the full-length toxins 31,62 . The deletion of amino acids 1769-1787 caused spontaneous autocleavage of subtype 2 TcdB in the absence of InsP6 63 . Here we demonstrate that the integrated CROPs domain forcibly protects TcsL from autoproteolysis by at least two mechanisms: the N-terminus of TcsL CROPs strongly restrains the autoproteolysis while longer CROPs further reduce the InsP6-induced autocleavage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the CROPs-truncated TcdA and TcdB underwent moderately increased InsP6-induced autocleavage compared to the full-length toxins 31,62 . The deletion of amino acids 1769-1787 caused spontaneous autocleavage of subtype 2 TcdB in the absence of InsP6 63 . Here we demonstrate that the integrated CROPs domain forcibly protects TcsL from autoproteolysis by at least two mechanisms: the N-terminus of TcsL CROPs strongly restrains the autoproteolysis while longer CROPs further reduce the InsP6-induced autocleavage.…”
Section: Discussionmentioning
confidence: 99%
“…TcdB2, B2Δ, and D270N were expressed in Bacillus megaterium (MoBiTec, Göttingen, Germany) and purified by nickel affinity chromatography (GE Life Sciences, Boston, MA) as previously described. 66 Purity and integrity were confirmed by SDS-PAGE and each batch of TcdB2 was tested for toxicity using a CHO cell killing assay. 67 …”
Section: Methodsmentioning
confidence: 99%
“… 53 After 5 h, mice were immunized subcutaneously (s.c.) with 10 μg B2Δ, a TcdB2 mutant incapable of entering host cells. 66 Unless stated otherwise, the B2Δ was adsorbed to a 2% w/v Alhydrogel alum adjuvant suspension (Invivogen, San Diego, CA) in PBS and is referred to as B2Δ/alum herein. Vaccines were divided equally over both flanks.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike CSPG4, FZD proteins do not possess glycosaminoglycan modifications or a known Ca 2+ -binding domain, which supports the notion that Ca 2+ could impact CSPG4 but not FZD tropism, with a greater effect on TcdB2. Second, previous studies from our lab identified a cell-penetrating peptide derived from amino acids 1769–1787 in TcdB2 that are necessary for cell binding and uptake ( 21 , 22 ). Interestingly, some cell-penetrating peptides are known to utilize glycosaminoglycans for cell entry ( 23 , 24 ), which would also be enhanced in the presence of Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%